Home equity extraction and the boom-bust cycle in consumption and residential investment - Xiaoqing Zhou (Bank of Canada, 2018)
The consumption boom-bust cycle in the 2000s coincided with large fluctuations in the volume of home equity borrowing. Contrary to conventional wisdom, I show that homeowners largely borrowed for residential investment and not consumption. I rationalize this empirical finding using a calibrated two-goods, multiple-assets, heterogeneous-agent life-cycle model with borrowing frictions. The model replicates key features of the household-level and aggregate data. The model offers an alternative explanation of the consumption boom-bust cycle. This cycle is caused by large fluctuations in the number of borrowers and hence in total home equity borrowing, even though the fraction of borrowed funds spent on consumption is small.
Keywords: D1; E2; E3; 330; Economic models; Housing; Credit and credit aggregates